Positive displacement machines : modern design innovations and tools - Sultan, Ibrahim A.; Phung, Truong H. (Academic Press, 2019)
Positive Displacement Machines: Modern Design Innovations and Tools explains the design and workings of a wide range of positive displacement pumps, compressors and gas expanders. Written at a mathematical and technical level, the book explores the most influential research in this field over the past decade, along with industry best practices. Sections highlight the importance of using the latest computation techniques and discuss how to follow the proper design procedures to achieve a desired outcome.